(untitled) (Al-Academy, 2024)
Pure continuity is one of the philosophical terms introduced by the French philosopher Henri Bergson. It means the transition from one state to another due to temporal, spatial and psychological factors. The researcher found that there are three types of continuity: qualitative, developmental, and expansive continuity. In this context, the researcher set an aim for the research that could be summarized as (unraveling the levels of pure continuity in the theatrical performance). Following the descriptive approach, the researcher analyzed a purposive sample taken from the performance of the play (Gilgamesh Who Saw), which was authored and directed by Dr. Hussein Ali Harif